Failure Analysis of A Fractured Connecting Rod - Mohammed, M.N; Omar, M.Z; Sajuri, Zainuddin; Salah, A; Abdelgnei, M.A; Salleh, M.S (Journal of Asian Scientific Research, 2012)
In many cases, the major reason behind or causing catastrophic engine failure is the occurrence of the connecting-rod failure and sometimes, such a failure can be attributed to the broken connecting rod’s shank especially when there is a probability of being pushed through the side of the crank-case, thereby making the engine irreparable. Thus, the major aim of the current work is to analyze the connecting rod failure. The study applied a finite element analysis and metallographic examination. Based on the findings, it was found that it is possible for each casting defect to develop depending on the cyclic loading behavior of the connecting rod into the start point for crack initiation before the occurrence of catastrophic failure.